Association between bullying victimization and health risk behavior in adolescents - Ana Beatriz Pacífico; Eliane Denise Araújo Bacil; Mariana Ardengue; Thiago Silva Piola; Michael Pereira da Silva; Fabio Fontana; Ademar Avelar; Wagner de Campos (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: The aim of this study was to examine the association between bullying victimization and health risk behaviors in adolescents. Methods: A representative sample of 1020 adolescents participated in the study. The variables such as bullying, health risk behaviors (tobacco, drugs, alcohol, sedentary behavior, smartphone use, level of physical activity, and sleep), and economic status were assessed using self-reported questionnaires. Odds ratios with 95% confidence intervals (95%CI) were obtained using binary logistic regression and ordinal, gross, and adjusted logistic regression (p<0.05). Results: Victims of bullying were more likely to smoke (OR 1.75; 95%CI 1.28-2.40), consume alcohol (OR1.43; 95%CI 1.05-1.94), have worse sleep quality (OR 1.94; 95%CI 1.28-2.91), and more sedentary behavior (OR 1.43; 95%CI 1.08-1.89) than those who were not bullied. However, victims were more likely to have high levels of physical activity than their non-bullied peers (OR 1.66; 95%CI 1.22-2.27). Conclusions: Bullying victimization was associated with an increased predisposition for the adoption of health risk behaviors. Interestingly, victims were also more prone to participate in physical activity.